Macroeconomic expectations and the time-varying stock-bond correlation: international evidence - Christian Conrad; Karin Loch (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
We explain the time-varying correlation between stock and bond returns by survey expectations on the future macroeconomic development. A modified DCC-MIDAS specification allows us to relate daily changes in the correlation to monthly expectations data. For a cross-section of countries, we show that the stock-bond correlation is mainly determined by expectations regarding the future course of monetary policy as well as stress in financial markets. From a European perspective, the asymmetry in the response of the stock-bond correlation to heightened stock market volatility in the UK, Germany and France on the one hand, and Italy on the other hand is of high policy relevance.
Keywords: E44; C32; C58; 330